Improving Cost Accounting and Internal Audit of Public Higher Education Institutions (Texas Journal of Multidisciplinary Studies, 2023)
In the article, equal and quality provision of education is widely recognized as an integral part of socio-economic development. Current theories offer different approaches to explain the impact of education, particularly adolescent education, on economic development.